Proletarian Imagination Self, Modernity, and the Sacred in Russia, 1910-1925 - Steinberg, Mark (Academic Studies Press, 2022)
In fin-de-siècle and early revolutionary Russia, a group of self-educated workers produced a large body of poetry and prose in which they attempted to comprehend their rapidly changing world. Witnesses to wars and revolution, these men and women grappled on paper with the nature of civilization and the imperatives of ethical truth. In a strikingly original approach to Russian culture, Mark D. Steinberg listens to their words, which are little known today. The results of their literary creativity, he finds, were frequently not what the new Soviet order was expecting from its workers, despite its celebration of the notion of a proletarian art
Description based on online resource; title from PDF title page (publisher's Web site, viewed 16. Dec 2024)
Keywords: LITERARY CRITICISM / Russian & Former Soviet Union